How Applicable is Lean Management for the NHS? - Walker, Gregory A. (2009)
The NHS is one of the worlds’ largest organisations, it started on the 5 July 1948 and provides public Healthcare for the United Kingdom. In light of recent events and the troubled UK economy, the NHS is likely to face budget constraints in the near future. This is something the NHS has not been used to in recent years, after around a decade of huge investment. With this in mind and the known efficiency issues within the NHS, which are often highlighted in the media. Action will need to be taken urgently in order for it to continue providing and improving its excellent service to customers. This research paper looks at how the use of ‘Lean’ can help the NHS achieve its aims by reducing non-value adding activity whilst still improving the services it offers. The aim is to find how applicable Lean Management is for the NHS. This paper will draw extensively from recent literature surrounding the subject including a number of case examples. In order to add to the growing literature the main body of this research paper will look at two aspects: